The effect of daily undulated periodization as compared to linear periodization in strength gains of collegiate athletes - Alvar, B.; Wenner, R.; Dodd, D. J. (The Journal of Strength and Conditioning Research, 2010)
Strength and conditioning coaches are always looking for ways to optimize gains in muscular strength. Previous resistance training research has examined the efficacy of non periodized multiple-set versus single-set, and linear as compared to non periodized multiple-set models on gains in muscular strength. Conversely, less research has examined the linear and undulating periodization models, especially when equating for volume and intensity. This study was designed to examine the effects of a linear periodization intervention as compared to a daily undulating periodization intervention on maximal strength gains in Division I athletes while controlling for volume and intensity. Twenty subjects were recruited from a Division I athletic program. All subjects performed a one repetition maximum (1RM) bench press test prior to beginning the training program and immediately upon completion of the six week training program. Participants were assigned to one of two groups, Linear Periodization (LP) or Daily Undulated Periodization (DUP). The LP group followed a plan that decreased volume of repetitions performed while increasing intensity (percent of 1RM) over the course of six weeks. The DUP group performed a high volume, low intensity workout; a medium volume and medium intensity workout; and a low volume, high intensity workout each week. Statistical analysis showed that there was a significant difference between the pre and post test results for both training models (p < 0.05), with the DUP group producing a slightly higher strength increase as compared to the LP group, however there was no statistically significant difference found between the training interventions (p > 0.05). DUP as well as LP will produce a significant training effect when implemented in a collegiate strength training program in a six week training cycle. This research study provides strength coaches scientific affirmation that different periodization models are an effective means of resistance training design for collegiate athletes. Both DUP and LP have been shown to increase muscular strength in the bench press in this population. This information gives the strength and conditioning coach some latitude in program design. Theoretically, variety in program design can alleviate the monotony that may occur during strength training for advanced athletes.